Dual Labour Market Theory Dalam Hubungan Bilateral Indonesia-Jepang: Analisis Penempatan Pekerja Migran Indonesia Program Specified Skilled Worker 2019-2024 - Tiorisma Nahampun; Glory Yolanda Yahya; Desri Gunawan (Iustitia: Journal of Legal Theory, Politics, and International Relations, 2026)
This study analyzes the placement of Indonesian Migrant Workers (PMI) through the Specified Skilled Worker (SSW) programme in Japan during 2019–2024 using Michael J. Piore’s Dual Labour Market Theory. The study employs a descriptive qualitative approach and library research method based on secondary data from academic literature, government publications, policy documents, and official statistics from Indonesia and Japan. The findings indicate that PMI placement increased substantially from 3,061 workers in 2019 to 44,298 workers in 2024, following a temporary decline during the COVID-19 period. In 2024, Indonesian workers were concentrated in elderly care, food and beverage processing, agriculture, industrial manufacturing, construction, and fisheries. These sectors share characteristics associated with the secondary labour market, including labour shortages, demanding working conditions, and relatively limited attractiveness to domestic workers. Japan’s ageing population and declining working-age population contributed to persistent structural labour demand, while Indonesia provided a significant supply of workers through bilateral labour cooperation. The findings support the applicability of Dual Labour Market Theory in explaining PMI placement through SSW as a structural response to labour shortages in Japan.